Mapeamento genético e estudo de genes candidatos para um modelo animal de doença neuromuscular - Daniel Almeida da Silva e Silva (2012)
A project called The mouse as a model organism - Induction of newmutations, developed in partnership by the Laboratory of Human and Animal Genetics (LGAH) Institute of Biological Sciences, UFMG and the Department of Immunology, Institute of Biomedical Sciences, USP, aimed at inducing of different mutations in the genome of mice using the mutagen N-ethyl-N-nitrosourea (ENU). In this project, we obtained 11 mutants with phenotypes of interest were selected for genetic mapping and positional cloning in order to generate animal models for human genetic diseases. Among the 11 mutant is the fraqueza (weakness).The fraqueza mutation is inherited as an autosomal recessive and ischaracterized by progressive loss of muscle strength and motor coordination in the tail and paws. The picture is observed from the first two weeks of life and the animal dies around the twelfth week. For purposes of mapping genetic animal BALB / c mice heterozygous for themutation weakness were crossed with C57BL / 6 normal generating F1 animals were then intercrossed generating recombinant animals F2.The present work was aimed at the medium-resolution mapping of the gene causing the phenotype weakness for linkage analysis in recombinant F2 animals, and characterization of genes Bullous Pemphigoid Antigen 1 (Bpag1) and Actin-related protein 1 homolog B (Actr1b), candidates positional and functional mutation. Linkage analysis was performed with the animals through recombinant polymorphic microsatellite markers for both strains (BALB / c and C57BL / 6), and themutation was mapped on chromosome 1 between markers D1mit373 (10.92 cM) and D1mit320 (18.64 cM), defining a region of 7.72 cM region is where the genes and Bpag1 Actr1b. It is hoped that this work was to identify the mutation responsible for the phenotype weakness so that this model can be used for future studies in neuromuscular and neurodegenerative diseases